2020
DOI: 10.3390/en13092293
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentary and Diagenetic Features and Their Impacts on Microbial Carbonate Reservoirs in the Fourth Member of the Middle Triassic Leikoupo Formation, Western Sichuan Basin, China

Abstract: In recent years, the discovery of two gas fields in the fourth member of the Leikoupo Formation in the Western Sichuan Basin of SW China confirmed the exploration potential of microbial carbonates. The aim of the present study is to clarify the formation mechanism of the microbial reservoirs in the Leikoupo Formation. For this purpose, lithofacies, depositional environments, and diagenesis analyses were performed in samples collected from cores of 12 wells. The climate of study area was arid during Anisian tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…Nowadays, a typical microbial carbonate reservoir has been found in the fourth member of the Leikoupo Formation in the Western Sichuan Basin 5 . From 2008 to 2012, well CK-1 and XS-1 have produced commercial gas flow at the rate of 86.8 × 10 4 m 3 /day and 68 × 10 4 m 3 /day respectively.…”
Section: Sedimentary Structures Of Microbial Carbonates In the Fourth...mentioning
confidence: 99%
See 2 more Smart Citations
“…Nowadays, a typical microbial carbonate reservoir has been found in the fourth member of the Leikoupo Formation in the Western Sichuan Basin 5 . From 2008 to 2012, well CK-1 and XS-1 have produced commercial gas flow at the rate of 86.8 × 10 4 m 3 /day and 68 × 10 4 m 3 /day respectively.…”
Section: Sedimentary Structures Of Microbial Carbonates In the Fourth...mentioning
confidence: 99%
“…In next year, well YaS-1 and YS-1 produced commercial gas flow at the rate of 48.5 × 10 4 m 3 /day and 60.32 × 10 4 m 3 /day respectively 6 . Although recent studies reached an agreement that the development of the microbial carbonate reservoir in the Leikoupo Formation was controlled by the sedimentary facies, there is also controversy over the sedimentary facies indentified by them 5,[7][8][9][10][11][12] . Some researches indicated that the microbial carbonate reservoir in the Leikoupo Formation is developed in tidal flat 9,10 , while some preferred microbial reef 7,8,11 , and others were inclined to microbial mound 5 .…”
Section: Sedimentary Structures Of Microbial Carbonates In the Fourth...mentioning
confidence: 99%
See 1 more Smart Citation
“…This facies association is interpreted as gypsiferous dolomitic and gypsiferous limy flats based on facies types, architecture, and stratigraphic position (Wang et al, 2020). In these flats, the brine surfaces responded to slow low‐amplitude sea level rise and fall, resulting in the interlacing of bedded evaporites and normal marine platform carbonate rocks.…”
Section: Stratigraphy and Facies Analysismentioning
confidence: 99%
“…Nowadays, a typical microbial carbonate reservoir has been found in the Fourth Member of the Leikoupo Formation in the western Sichuan Basin (Wang et al, 2020). From 2008 to 2012, well CK-1 and XS-1 have produced commercial gas ow at the rate of 86.8×10 4 m 3 /day and 68×10 4 m 3 /day respectively.…”
Section: Introductionmentioning
confidence: 99%